Students' Self-Disclosure - Wan Chalidaziah; Herman Nirwana; Alizamar Alizamar (Fakultas Ilmu Pendidikan UNP)
The purpose of this research is to examine the comparison of students' self-disclosure based on gender. The Comparative descriptive design was applied in this research. The research population was the students of guidance and counseling in Acehnese. The sample consists of 169 students (53 male and 116 female) with proportional random sampling technique. The research instrument used Scale Self-Disclosure in reliability 0.910. The Data Analyzed by using ANOVA. The result of determined that there are significant differences between students' self-disclosure are observed from gender.